KEPEKAAN PERTUMBUHAN SETEK CABANG KAYU MANIS (Cinnamomum burmanii Blume) TERHADAP ROOTONE-F, AIR KELAPA MUDA DAN BAWANG MERAH - Basir Achmad (Jurnal Hutan Tropis, 2019)
Utilizing natural growth regulatorshas been developed widely beside utilizing the artificial one.  Comparing the two growth regulators is needed in order that it is found  more effective ones on the cutting growth. The study aimed to analyze the growth sensitivity of cinnamon cuttings on Rootone-F (synthetic hormones),coconut water and red onion extract (natural hormones). A completely randomized design was employed in the experimental design. The analysis of variance was done with theStatistical Package for Social Sciences 17.0 software aid. The results showed that thegrowthvariables of cinnamon: the budding rates were sensitive to the red onion treatment, and the length of roots were sensitive to the coconut water treatment. Yet, the overall results showed that the Rootone-F treatment provided constant effects on increasing the the growth of branch cuttings of cinnamon. The most important factor determining the success of cutting growth is root growth. The highest percentage growth of roots (90%) was achieved through the treatment of Rootone-F with a dosage of 30 mg/cut. However, its effects did not differ from the effects of other treatments.Keywords: cinnamon cuttings; Rootone-F, young coconut water, red onion extract